Multi-omics analysis reveals ThMYB6 regulation of flavonoid biosynthesis in differently colored tuberous roots of Tetrastigma hemsleyanum - Yang, Feng; Xing, Qiaoyue; Liu, Shouzan; Gu, Yiwen; Wang, Ziyue; Wang, Hongyan; Shen, Qiong; Li, Shan; Feng, Bojie; Bai, Yan (Frontiers in Plant Science, 2025)
IntroductionTetrastigma hemsleyanum Diels et Gilg (Vitaceae) is a medicinally valuable plant typically with a whitish root cross-section. Resource surveys discovered some roots of T. hemsleyanum with a yellow-brown root cross-section and stronger antioxidant properties. However, the molecular mechanisms underlying these phenotypic differences remain poorly understood.MethodsWe employed integrated metabolomic and transcriptomic analyses to compare the two root types. Key candidate genes were cloned and functionally characterized to uncover the regulatory mechanisms involved.ResultsMetabolomic analysis identified significant changes in 217 metabolites between the two types, among which 57 flavonoids, such as Hesperetin-7-O-glucoside, were significantly higher in the yellow-brown roots. Transcriptomic analysis revealed 3516 differentially expressed genes, many associated with flavonoid biosynthesis. Differences in root quality were largely attributed to varied flavonoid production. Analysis of transcription factors regulating this process identified a strong correlation between MYB6 genes and flavonoids biosynthesis. Functional analysis indicated that the ThMYB6 factor of the R2R3 MYB subgroup 5 regulates flavonoid production in T. hemsleyanum.ConclusionThe ThMYB6-mediated divergence in flavonoid biosynthesis is the key factor influencing quality differences between the two phenotypes. These results establish a theoretical foundation for targeted quality improvement and offer scientific support for the medicinal development of T. hemsleyanum.